2020
DOI: 10.1186/s12933-020-01101-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bempedoic acid for prevention of cardiovascular events and diabetes: a systematic review and meta-analysis

Abstract: Background: Bempedoic acid is an oral, once-daily, first-in-class drug being developed for the treatment of hyperlipidemia. However, evidence of bempedoic acid use for the prevention of cardiovascular events and diabetes is lacking. Thus, we aim to evaluate the benefit and safety of bempedoic acid use for the prevention of cardiovascular events and diabetes. Methods: We searched Medline, Embase, and the Cochrane Central Register of Controlled Trials with no language restriction from inception until March 3, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
1
41
0
9
Order By: Relevance
“…It has been Several pooled analyses of trials investigating effects of BA have been performed at the same time by other groups. [26][27][28][29][30] The majority of those focused on BAs capacities in lipid-lowering with comparable results to the current analysis: Allocation to BA as compared with placebo led to highly significant reductions in major atherogenic lipid fractions of LDL-C, non-HDL-C and apoB. [26][27][28][29] In contrast, primary interest of the current meta-analysis was to assess evidence on BAs efficacy in improving relevant clinical outcomes, which is the fundamental objective of pharmacological lipid-lowering.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It has been Several pooled analyses of trials investigating effects of BA have been performed at the same time by other groups. [26][27][28][29][30] The majority of those focused on BAs capacities in lipid-lowering with comparable results to the current analysis: Allocation to BA as compared with placebo led to highly significant reductions in major atherogenic lipid fractions of LDL-C, non-HDL-C and apoB. [26][27][28][29] In contrast, primary interest of the current meta-analysis was to assess evidence on BAs efficacy in improving relevant clinical outcomes, which is the fundamental objective of pharmacological lipid-lowering.…”
Section: Discussionmentioning
confidence: 63%
“…[26][27][28][29] In contrast, primary interest of the current meta-analysis was to assess evidence on BAs efficacy in improving relevant clinical outcomes, which is the fundamental objective of pharmacological lipid-lowering. The current work is, along with another recent publication, 30 the first to provide information on this.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis combined the outcome of new-onset or worsening diabetes in these four trials which reported 3.7% of individuals taking bempodic acid compared to 5.7% of individuals on placebo [ 34 ]. Bempodeic acid was associated with a risk reduction of 0.65 (95% CI 0.44–0.96; I 2 = 23%) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the use of fibrates as lipid-lowering therapyhas demostrated no significant cardiovascular benefit [ 43 ]. Nonetheless, other drugs such as bempedoic acid and ezetimibe have shown favourable cardioprotective outcomes [ 34 , 43 ]. Given the undisputed causal relationship between LDL-C and ASCVD [ 8 ] with no known level below which further LDL-C lowering ceases to be beneficial [ 44 ], the significant LDL-C reduction with bempedoic acid provides clear hope and the expectation that these data will be translated into a reduction in ASCVD events and subsequent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…ETC-1002 (8-hydroxy-2,2,14,14-tetramethylpentadecanedioic acid), previously known as ESP55016 or bempedoic acid, is a novel drug under development for the treatment of dyslipidemia. ETC-1002 has been shown to improve lipid pro les and signi cantly attenuate levels of glucose via the activation of AMPK in multiple animal models [21,22]. Moreover, ETC-1002 was found to regulate immune responses and adipose tissue in ammation via the LKB1-dependent activation of AMPK in macrophages [23].…”
Section: Introductionmentioning
confidence: 99%